The role of information and communication technologies in the development of management manpower in Nigeria (2012)
In Nigeria, there are management instituitions which are saddled with management manpower preparation. It is an obvious fact that in management, as in other sectors of the economy, the role of Information and Communication Technology (ICT) cannot be over-emphazied. ICTs are a diverse set of tools and resources used to communicate, create, disseminate, store, and manage information. Thus, the paper attempted to investigate the role of ICT in the preparation of management of human capital for the economy. A rating scale on the role of ICT in management preparation developed and validated by the researchers was administered on a sample of 250 management trainees and 50 management educators in a specialized management institution in Nigeria. Findings showed that ICT played significant role in the development of managers for the Nigerian economy; ICT had significantly improved teaching and learning in management courses and the trainees' achievement in courses like planning, statistics, management communication, quantitative analysis and operations research. It was recommended that every institution involved in management development should be sent on practical exposure programmes outside the institution to enhance their knowledge and application of ICTs in management practices.